A Study of Health Literacy and Clinical Outcomes of Older Adults with Hypertension and Diabetes in Northeastern Communities, Thailand - Ratchanee Piwpong, Supaporn Marungsee, Thripnaraporn Sungsrikaw, Boonyika Jhornlumkone, (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Health literacy is a crucial factor in self-management of health which affects older adults’ behaviors and health outcomes. This study is a cross sectional descriptive research aimed at studying health literacy, correlations between personal factors and health literacy and correlations between health literacy and clinical outcomes among older adults with hypertension and diabetes in northeastern communities of Thailand. The findings revealed four personal factors were positively correlated with health literacy among older adults with hypertension and diabetes consisting of gender (c2 =6.16, p < 0.05), age (c2 =7.53, p < 0.05), income sufficiency (c2 =11.88, p < 0.05) and cognitive capacity (c2 =13.43, p < 0.001). Health literacy was correlated with performance of 3 Or. 2 Sor. behaviors with statistical significance (c2 =5.88, p < 0.05) and health literacy was correlated with clinical outcomes such as triglyceride (r = -.19, p < 0.05) and risk of stroke and cardiovascular disease in the future (CVD Risk Score) (r = -.18, p < 0.05) with statistical significance. In improving health literacy, healthcare teams should give consideration to older age, income sufficiency and cognitive capacity to help older adults gain health literacy to the level of literacy and effective self-care along with improving health literacy among hypertensive older adults for good health behaviors in order to reduce triglyceride levels and risk of stroke and cardiovascular disease in the future.